2009
DOI: 10.1099/vir.0.016964-0
|View full text |Cite
|
Sign up to set email alerts
|

Beta interferon plus gamma interferon efficiently reduces acyclovir-resistant herpes simplex virus infection in mice in a T-cell-independent manner

Abstract: Acyclovir (ACV)-resistant herpes simplex virus type 1 (HSV-1) causes severe diseases in immunocompromised patients, so identification of new therapies is needed. Interferons (IFNs) are used to treat several other viral infections in the clinic, and IFN-b and IFN-c are known to cooperatively reduce wild-type HSV-1 replication in the corneas of immunocompetent mice. Because IFN-c has been shown to exert an antiviral effect mostly through T cells, whether combined IFN treatment can still inhibit ACV-resistant HSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The transient induction of host innate responses may explain the reduced viral titer detected during acute infection compared to that detected during persistent infection. Our previous in vitro study (37) showing that tkLTRZ1 is susceptible to treatments with type I interferons (interferon alpha or beta) and especially the combination of type I (interferon beta) and type II (interferon gamma) interferons supports this possibility.…”
Section: Discussionmentioning
confidence: 52%
“…The transient induction of host innate responses may explain the reduced viral titer detected during acute infection compared to that detected during persistent infection. Our previous in vitro study (37) showing that tkLTRZ1 is susceptible to treatments with type I interferons (interferon alpha or beta) and especially the combination of type I (interferon beta) and type II (interferon gamma) interferons supports this possibility.…”
Section: Discussionmentioning
confidence: 52%
“…Fortunately, the combined use of IFN‐β with IFN‐γ was shown to be highly effective in reducing mutant virus replication in cell cultures and in vivo in mice [Huang et al . (119)]. The researchers suggested that for therapy, frequent IFN treatment or IFN together with anti‐HSV drugs, such as foscarnet, which target viral DNA polymerase, could be used.…”
Section: Ifn: Immune Antiviral Activity and Relation To Hsv1 And Admentioning
confidence: 99%
“…However, IFN-g alone may have limited efficacy in immunocompromised HSV-1-infected individuals lacking a robust adaptive immune response. Recent studies have shown that when immunocompromised nude mice are infected with a DAA (acyclovir)-resistant HSV-1 variant and treated with IFN-b in combination with IFN-g, viral infection is reduced [65]. These preliminary data are in further support of the broadspectrum antiviral activities of IFNs-a/b.…”
Section: Ifn Therapy For Highly Transmissible Viral Infectionsmentioning
confidence: 76%
“…For immunocompromised individuals infected with HSV-1, viral pathogenesis can lead to serious life-threatening disease; more so in the context of emergent drug-resistant HSV-1 strains [65][66][67]. Different DAAs have been used to control HSV-1 infection, including acyclovir, penciclovir and foscarnet, resulting in the emergence of DAA-resistant HSV-1 strains [65][66][67]. IFN-g is able to exert antiviral activity by stimulating a T cell response.…”
Section: Ifn Therapy For Highly Transmissible Viral Infectionsmentioning
confidence: 99%